Designing a Framework of Components to Support Patient Engagement in Research - Öfelein, Matthias; Reichold, Michael; Maier, Christian; Prokosch, Hans-Ulrich (German Medical Data Sciences: Shaping Change – Creative Solutions for Innovative Medicine, 2019)
In the context of the German Medical Informatics Initiative (MII), where data reuse and data sharing are major goals, cross-site, long-term research on patient care data can only be conducted lawfully with informed patient consent. Thus, the MII consent working group developed a template form for patient information and broad consent based on work that has been done for a former biobank project. The broad consent enables the patient to consent to the use of a wide range of the documented data including research purposes. Therefore, a user-friendly tool is needed which not only supports the storage and maintenance of the patient's consents but also allows him to easily review or withdraw his consents. Furthermore, the tool should allow the patient to review the use of his data in research projects and possible publications. This is why we developed a concept of how such a tool could be integrated into the clinical and research system landscape and implemented a prototype as a proof of concept.
CRIS-Team Scopus Importer:2019-09-24
Keywords: Consent Management; Data Sharing; Informed Consent; Patient Participation